Comparison of Self-Etching Adhesives and Etch-and-Rinse Adhesives on the Failure Rate of Posterior Composite Resin Restorations: A Systematic Review and Meta-Analysis - Vieira, Basílio Rodrigues; Dantas, Eugênia Lívia de Andrade; Cavalcanti, Yuri Wanderley; Santiago, Bianca Marques; Sousa, Frederico Barbosa de (European Journal of Dentistry, 2021)
The aim of this study was to perform a systematic review with meta-analysis on the comparison of self-etching adhesives and etch-and-rinse adhesives with respect to the failure rate of posterior composite resin restorations. The study protocol was registered in PROSPERO (CRD42017078015), following PRISMA recommendations and PICO search strategy. Literature search was performed in the following databases: MEDLINE, ISI Web of Science, LILACS, SCOPUS, and Cochrane Library through July 2021. Six studies from five randomized clinical trials were included in the qualitative synthesis. The funnel plot detected important bias (all studies out of the funnel area). The meta-analysis showed a positive summary Cohen H effect size of 0.406 (95% CI: 0.100; 0.713, p = 0.009), favoring etch-and-rinse adhesives. The total number of failures (including restorations that required replacement and those that did not require replacement) were attributed to either marginal adaptation (five studies) or marginal staining (one study). A very low certainty of the evidence was obtained through GRADE analysis. In conclusion, current available evidence indicates that etch-and rinse adhesives performed better (with a low effect size) than self-etching adhesives in terms of failure rates in posterior composite restorations.
Keywords: dentine adhesives; resin composite; dental restoration; failures; clinical studies; meta-analysis